Ideology and Brand Consumption - Khan, Romana; Misra, Kanishka; Singh, Vishal (Psychological Science, 2013)
Do mundane daily choices, such as what brands people buy in a supermarket, reflect aspects of values and ideologies? This article presents a large-scale field study performed to determine whether traits associated with a conservative ideology, as measured by voting behavior and religiosity, are manifested in consumers’ routine, seemingly inconsequential product choices. Our analysis of market shares for a variety of frequently purchased products shows that both of these measures of conservatism are associated with a systematic preference for established national brands (as opposed to their generic substitutes) and with a lower propensity to buy newly launched products. These tendencies correspond with other psychological traits associated with a conservative ideology, such as preference for tradition and the status quo, avoidance of ambiguity and uncertainty, and skepticism about new experiences.